Aktualisasi Kearifan Lokal Pojhien Jhengngato’ Melalui Pendekatan Experiential Learning - Dilla Fadila; Siti Komariah; Sardin Sardin (Jurnal Paedagogy, 2023)
This study aims to describe the application of experiential learning conducted by Baiturrahman Islamic High School to preserve the local wisdom of pojhien jhengngato'. This research method used case studies with a qualitative approach. Purposive sampling techniques were used to select informants. Data collection in this study used observation, interview, and documentation techniques. This research data analysis technique used interactive models from the Miles and Huberman Model. Testing the validity of the data was carried out by triangulation of sources. The results showed that Baiturrahman Islamic High School had implemented experiential learning to preserve pojhien jhengngato's local wisdom. It was done by inviting pojhien jhengngato' to the Sumenep Regency anniversary commemoration event at Baiturrahman Islamic High School. Furthermore, the assignment of a practical exam in the form of writing an essay on local wisdom pojhien jhengngato' was carried out with techniques according to Kolb, which consists of stages: 1) the stage of real experience, 2) reflection observation stage; 3) conceptualization stage; and 4) the implementation stage.